Liver Fibrosis and Steatosis in Virally Suppressed HIV-Infected Patients with Cytomegalovirus Seropositivity - Chyntia Olivia Maurine Jasirwan; Adik Wibowo; Amal C Sjaaf; Gita Aprilicia; Dyah Purnamasari; Evy Yunihastuti; Rino Alvani Gani (The Indonesian Society for Digestive Endoscopy, 2021)
Background: Cytomegalovirus (CMV) is a human herpesvirus common in people with human immunodeficiency virus (HIV). In a patient with immunocompetence, long periodic asymptomatic CMV might affect to develop the abnormal liver function and contribute to non-AIDS defining morbidity, including chronic liver disease. This study aims to know the prevalence of liver fibrosis and steatosis in virally suppressed HIV infected patients with CMV reactive and summarize the correlation of clinical presentation with liver fibrosis and steatosis in these subjects.Method: A cross-sectional study in HIV Integrated Care Unit, Cipto Mangunkusumo Hospital, was conducted from April 2019 until June 2020. Subjects enrolled in this study were suppressed HIV patients aged between 30-40 years with positive IgG CMV and already using stable ART for at least one year. Transient elastography measured the liver stiffness. Patients with liver stiffness above 7 kPa were defined as having significant liver fibrosis. In addition, Spearman correlation was conducted to evaluate the correlation of clinical presentation of subjects related to liver fibrosis and steatosis. Results: A total of subjects was included in this study. Dominantly male (62.5%) with average age 38 ± 4.68 years. The median amount of CMV DNA was 466 (17-21284) copy/ml. Significant Fibrosis was found in 17/80 (21%) subjects. In this study, clinical parameters correlated with liver fibrosis were insulin, glucose fasting, Homa IR, triglyceride, HDL, and platelet. A medium positive correlation was found in insulin, and Homa IR, with coefficient correlation for insulin, was r = 0.475, p 0.001; and coefficient correlation for Homa IR was r = 0 .487, p 0.001.Conclusion: The prevalence of liver fibrosis was 12% in these subjects. In addition, insulin and Homa IR had a positive correlation with increasing liver fibrosis.